Sistem Penanggulangan Kebakaran di Rumah Sakit - Shifa Aulya Hadi Ramadhan; Anik Setyo Wahyuningsih (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
In 2020-2022, there were fires in 15 hospitals around the world that handled COVID-19, causing 280 deaths. In Indonesia, there were 8 hospital fires during July to October 2020. Hospital fires pose a high risk because most of the hospital residents are patients undergoing treatment so their physical condition is unable to carry out rescue measures and relies on medical equipment. This research aims to determine the implementation of the fire control system at Regional General Hospital of Salatiga City. This research is a type of descriptive research with qualitative methods. The informants in this research consisted of 3 main informants and 4 triangulation informants. Data collection techniques were carried out through observation, interviews and documentation studies. The data analysis used is univariate analysis. The research results showed that of the total of 90 indicators, 79% (71 indicators) had been fulfilled and 21% (19 indicators) had not been fulfilled. Fire control system at Regional General Hospital of Salatiga City is included in the adequate category. Most of the fire control system components function well, but there are several other utility sub-components that function imperfectly or do not comply with the specified requirements.